Selection on female reproductive schedules in the marula fly, Ceratitis cosyra (Diptera: Tephritidae) affects dietary optima for female reproductive traits but not lifespan - Malod, Kevin; Archer, C. Ruth; Hunt, John; Nicolson, Susan W.; Weldon, Christopher W. (Frontiers in Insect Science, 2023)
Environmental fluctuations can select on life-history traits and trade-offs. As the environment shifts, changes in phenology may alter the availability of host-plants. This may affect when and how much herbivorous insects should invest in survival and reproduction. In environments where adult mortality risk rises, organisms should shift their nutrient intake towards a ratio that favours reproduction at the expense of lifespan. However, we lack empirical work testing whether shifts in the timing of oviposition trigger altered nutrient intake and, in turn, life-history strategies. Here, in the marula fruit fly, Ceratitis cosyra, we tested how upward-selection on the age of female oviposition, in comparison with laboratory adapted control flies, affects the sex-specific relationship between protein and carbohydrate intake and life-history traits including lifespan, female lifetime egg production and daily egg production. We then determined the macronutrient ratio consumed when flies from each selection line and sex were allowed to self-regulate their intake. Lifespan, lifetime egg production and daily egg production were optimised at similar protein to carbohydrate ratios in flies from both selection lines. Likewise, females and males of both lines actively defended similar nutrient intake ratios (control =1:3.6 P:C; upward-selected = 1:3.2 P:C). These results are comparable to those in non-selected C. cosyra, where the optima for each trait and the self-selected protein to carbohydrate ratio observed were nearly identical. The nutrient blend that needs to be ingested for optimal expression of a given trait appeared to be well conserved across laboratory adapted and experimentally selected populations. These results suggest that in C. cosyra, nutritional requirements do not respond to a temporal change in oviposition substrate availability.